Seas and waterways of the world an encyclopedia of history, uses, and issues - Zumerchik, John; Danver, Steven Laurence; Gale Group (Santa Barbara, Calif. ABC-CLIO, 2010)
Provides the history of the ways human beings have used the world's waterways for business, protection, and recreation.
v. 1. History of the world's seas and waterways. Uses of the world's seas and waterways -- v. 2. Uses of the world's seas and waterways. Issues pertaining to the world's seas and waterways.
Electronic reproduction.
Keywords: Waterways -- Encyclopedias; Seas -- Encyclopedias; Electronic books